A Thermodynamic Study of Aqueous 1‐Allyl‐3‐Methylimidazolium Formate Ionic Liquid as a Tailored Sorbent for Carbon Dioxide Separation. Issue 8 (23rd March 2017) - Xie, Yujiao; Raut, Dilip G.; Samikannu, Rakesh; Mikkola, Jyri‐Pekka; Ji, Xiaoyan
Abstract: In this work, aqueous 1‐allyl‐3‐methylimidazolium formate ([Amim][HCOO]) was studied as a potential sorbent for CO2 separation. The density and viscosity of aqueous [Amim][HCOO] were measured at temperatures ranging from 293.15 to 333.15 K at atmospheric pressure. The solubility of CO2 and CH4 in dry [Amim][HCOO] as well as the CO2 solubility in aqueous [Amim][HCOO] were measured at pressures up to 1.8 MPa and temperatures of 298.2, 313.2, and 333.2 K. The results showed that the density and viscosity of aqueous [Amim][HCOO] as well as the CO2 solubility in aqueous [Amim][HCOO] decreased upon increasing the water concentration and temperature. The viscosity was very sensitive to the water concentration. The experimental density and viscosity of aqueous [Amim][HCOO] were fitted to semiempirical equations, and the excess molar volume and viscosity deviations were calculated to investigate the interaction between the [Amim][HCOO] ionic liquid and water. The experimental vapor–liquid equilibrium was represented with the nonrandom two‐liquid and Redlich–Kwong model. The model parameters can be further implemented into Aspen Plus software to conduct process simulations. Abstract : Soaking it all in : A thermodynamic study is performed to investigate 1‐allyl‐3‐methylimidazolium formate ([Amim][HCOO]) as a liquid sorbent for CO2 separation. The properties and gas solubility in aqueous [Amim][HCOO] are studied.